PENGARUH LABA AKUNTANSI, ARUS KAS OPERASI, DAN UKURAN PERUSAHAAN TERHADAP RETURN SAHAM PADA PERUSAHAAN TELEKOMUNIKASI YANG TERDAFTAR DI BEI - Zebua, Jeliston; Susanthi, Putu Rani (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2023)
This research aims to determine the effect of accounting profit, operating cash flow and company size partially. . The data analysis technique was carried out using multiple linear regression. The results of this analysis are that accounting profit has a significant effect on stock returns, operating cash flow has a significant effect on stock returns, while company size has no effect on stock returns because the size of the company is not all that can be seen by investors. based on the results of the F count test of 0.073 with a significance of 0.028 less than 0.05, it can be said that simultaneously accounting profit, operating cash flow and company size affect stock returns in telecommunications companies listed on the Indonesia Stock Exchange in 2017 - 2021.